The development and psychometric assessment of communication skills checklist for 6- to 24-month-old Persian children. Issue 2 (3rd April 2023) - Bayat, Narges; Ashtari, Atieh; Vahedi, Mohsen
Abstract: Prelinguistic skills play an important role in children's communication development. These skills are considered as significant bases for language acquisition and function conductive to later social development. Means of communication, communicative functions, skills with cognitive bases, and language comprehension are important prelinguistic skills. There is a critical period for acquiring prelinguistic skills and early identification of communication deficits is an important issue to be considered. The present study aimed to develop a communication skills checklist for Persian children aged 6- to 24-month-old and evaluate its psychometric properties. Parents of 277 Persian children aged 6- to 24-month-old participated in the current study. A checklist was first developed after an extensive literature review and various psychometric analyses in addition to regression analyses were carried out to determine its validity and reliability. The final checklist contained 36 items with high face validity and content validity (CVI > 0.62, CVR > 0.79). Also, the checklist demonstrated a high association with the CNCS (Pearson's correlation coefficient = 0.85, p < 0.001), and the construct validity showed significant differences between the four age groups ( F -test = 197.881, p < 0.001). The results of the internal consistency measurement (Cronbach's alpha coefficient = 0.952) and the test-retest reliability test (ICC = 0.933, p < 0.001) revealed excellent reliability of the checklist. In conclusion, based on the psychometric assessment, this checklist is a promising tool for assessing communication skills in Persian children aged 6 to 24 months.